CADRE ASSISTANCE IN PROMOTIVE AND PREVENTIVE DENTAL HEALTH PROGRAMS IN TRADITIONAL COMMUNITIES OF KAMPUNG NAGA - Eliati Sri Suharja; Aan Kusmana (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Kampung Naga is one of the traditional villages in Neglasari Village, Salawu District, Tasikmalaya Regency. The Kampung Naga Traditional Community is known for its strength in maintaining and preserving the traditions of its ancestral heritage. As a traditional village, the lives of its people are inseparable from traditional rules, including regarding health. Self-cleaning activities such as bathing are carried out in the